Peruvian Agrarian Reform. A New Legal Ideology? - Bustamante Belaúnde, Alberto (1974)
In order to conduct an analysis of the legal changes occurring in a specific country, it is imperative to approach the study autonomously and detached from external influences. However, in certain circumstances, it is pertinent to incorporate an observation of social and economic phenomena to obtain a more complete understanding and a more precise explanation of the legal phenomena that arise in the legal environment. The main objective of this paper is to examine the transformations that have taken place in the Peruvian legal system in the years before 1973. In this context, it proposes an exhaustive analysis of both the conceptual bases that sustain the traditional legal ideology and the socio-legal dynamics that arose because of the agrarian reform in Peru. The aim is to show how the reform has had an impact on these conceptual bases. By means of this analysis, the conclusion is reached that an adequate conceptualization of law necessarily requires reflecting the surrounding reality, without seeking to distance from it.